GREEN TECHNIQUES IN SYNTHESIS OF SOME THIAZOLIDINONES (International Journal of Pharmaceutical Sciences and Drug Research, 2017)
A survey of synthesis of thiazolidine derivatives has revealed that the thiazolidine nucleus has fascinated the chemists, pharmacologist and the researchers because of the biological responses exhibited by these compounds. This has led to designing the synthesis of a variety of such derivatives that are of high interest from the point of view of their bioactivity. Attempts were made by the researchers to synthesize these derivatives both by conventional methods as well as greener approach. Present study on the literature survey of thiazolidine derivatives emphasizes only eco-friendly methods of producing these derivatives. Purpose of this study is to create an enthusiasm among medicinal chemists, biochemists and the researchers to design synthesis of potential bioactive agents in a greener way.